Audit Pemerintah dan Indikasi Tindak Pidana Korupsi - Iqbal Tejokusumo; Nelyumna Amyulianthy; Rafrini Amyulianthy (JRB-Jurnal Riset Bisnis, 2022)
Evidence of poor governance in a country because the weakness of government's role in managing public resources which can be addressed by the phenomenon of corruption. Thus, the need for monitoring from an independent bodies to examine the financial accountability of state finances to the public. The purpose of this study was to determine the effect of audit finding, follow-up audit, and audit opinion on indication of corruption. This research was conducted at the Indonesian provincial government with a purposive sampling method. Samples obtained were 33 provincial governments from 34 provincial governments with 3-year observation period. The data was obtained by taking from the Summary Reports of Supreme Audit Board RI (BPK-RI), the Provincial Government Financial Report, and the Attorney General of Indonesia Annual Report in 2014-2016. The technique way used by multiple regression analysis with data panel approached. The findings showed that the Audit Findings has a significant positive effect on indication of corruption, meanwhile the follow-up audit and audit opinion has a significant negative effect on indication of corruption.